Veterinarians 'sans frontieres' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The veterinarians, engineers, agronomists and technicians of the NGO Veterinaires sans frontieres, work directly with livestock herders and rural communities to help save threatened herds. As part of their field activities, they deal with both the...